CyPPA, a Positive SK3/SK2 Modulator, Reduces Activity of Dopaminergic Neurons, Inhibits Dopamine Release, and Counteracts Hyperdopaminergic Behaviors Induced by Methylphenidate1 - Herrik, Kjartan F.; Redrobe, John P.; Holst, Dorte; Hougaard, Charlotte; Nielsen, Karin S.; Nielsen, Alexander N.; Ji, Huifang; Holst, Nina M.; Nielsen, Elsebet Ø.; Strøbæk, Dorte; Christophersen, Palle (Frontiers in Pharmacology, 2012)
Dopamine (DA) containing midbrain neurons play critical roles in several psychiatric and neurological diseases, including schizophrenia and attention deficit hyperactivity disorder (ADHD), and the substantia nigra pars compacta neurons selectively degenerate in Parkinson’s disease. Pharmacological modulation of DA receptors and transporters are well established approaches for treatment of DA-related disorders. Direct modulation of the DA system by influencing the discharge pattern of these autonomously firing neurons has yet to be exploited as a potential therapeutic strategy. Small conductance Ca2+-activated K+ channels (SK channels), in particular the SK3 subtype, are important in the physiology of DA neurons, and agents modifying SK channel activity could potentially affect DA-signaling and DA-related behaviors. Here we show that CyPPA (cyclohexyl-[2-(3,5-dimethyl-pyrazol-1-yl)-6-methyl-pyrimidin-4-yl]-amine), a subtype-selective positive modulator of SK channels (SK3 > SK2 >>> SK1, IK), decreased spontaneous firing rate, increased the duration of the apamin-sensitive, medium duration afterhyperpolarization (mAHP), and caused an activity-dependent inhibition of current-evoked action potentials in DA neurons from both mouse and rat midbrain slices. Using a immunohistochemically and pharmacologically validated DA release assay employing cultured DA neurons from rats, we show that CyPPA repressed DA release in a concentration-dependent manner with a maximal effect equal to the D2 receptor agonist quinpirole. In vivo studies revealed that systemic administration of CyPPA attenuated methylphenidate-induced hyperactivity and stereotypic behaviors in mice. Taken together, the data accentuate the important role played by SK3 channels in the physiology of DA neurons, and indicate that their facilitation by CyPPA profoundly influences physiological as well as pharmacologically induced hyperdopaminergic behavior.